Comparison of Level of Fatigue and Disease Correlates in Patients With Rheumatoid Arthritis and Systemic Sclerosis - Kevser GÖK,; Kemal EROL,; Gizem CENGİZ,; Salih ÖZGÖÇMEN, (Archives of Rheumatology, 2018)
Objectives: This study aims to compare the levels of fatigue in patients with rheumatoid arthritis (RA) and systemic sclerosis (SSc) and to assess the potential influence of fatigue on clinical variables. Patients and methods: Age- and sex-matched adult patients with SSc (n=50; 6 males, 44 females; mean age 47.7 years; range 23 to 72 years) and RA (n=51; 6 males, 45 females; mean age 50.8 years; range 23 to 71 years) were consecutively recruited. Patients were examined and evaluated for disease specific and generic outcome measures including disease activity parameters, physical functions, psychological status, and health related quality of life measures. Level of fatigue was assessed by Fatigue Severity Scale and Multidimensional Assessment of Fatigue scale. These were interviewed by the same experienced physician who was blind to clinical data. Results: Patients had similar educational and smoking status, as well as functioning and health related quality of life. However, patients with RA declared higher levels on visual analog scale-pain (p=0.012) and higher body mass index than patients with SSc (p<0.0001) and lower distances in six-minute walking test (p=0.002). Levels of fatigue were quite similar between patients with RA and SSc. Levels of fatigue, measured by different scales, were significantly correlated with physical functions and health related quality of life measures and psychometric variables in both groups; however, the correlation coefficients were relatively higher in patients with RA. Conclusion: Fatigue is a major problem in patients with RA and SSc. Our findings revealed that level of fatigue was quite similar between patients with RA and SSc and significantly correlated with physical functions and health related quality of life. Patients with RA and SSc should be carefully evaluated for fatigue by using valid scales and the impact of fatigue on clinical measures should not be overlooked.